Diversity climate on turnover intentions: a sequential mediating effect of personal diversity value and affective commitment. Issue 5 (20th August 2020) - Lee, Joonghak; Kim, Steven; Kim, Youngsang
Abstract : Purpose: Research on diversity climate has shown that diversity climate as an employee's perception of an organization's diversity-related practices or procedures has a positive impact on reducing turnover intentions. However, we know little about which intervening mechanism explains the relationship between diversity climate and employee's turnover intentions. In this study, we suggest that individual employee's perceived diversity climate influences turnover intentions through personal diversity value and affective commitment. Design/methodology/approach: With a sample of 901 employees in more than 50 companies affiliated in South Korea, the authors test the hypothesized relationship, using structural equation modeling (SEM). Findings: Our findings show that personal diversity value and affective commitment sequentially mediate the relationship between perceived diversity climate and turnover intentions. Research limitations/implications: This study can enhance the understanding about the mediating mechanism linking the relationship between perceived diversity climate and turnover intentions and how personal diversity value and affective commitment link the relationship. Originality/value: The authors theorize and find that perceived diversity climate can influence personal diversity value that results in employee commitment and turnover intentions.